Radiolabeling of and macromolecular syntheses in Neisseria gonorrhoeae types 1 and 4. - Lim, D V (1977)
Type 1 and type 4 cells of Neisseria gonorrhoeae were grown in a liquid medium that maintained colony type for several hours. Organisms from both types of colonies incorporated labeled glucose, as well as nucleic acid and protein precursors, into specific cellular fractions during growth in the medium. Ribonucleic acid and protein were synthesized actively by the bacteria, with incorporation of label chased by the addition of unlabeled precursors. The method can be used to label type 1 and type 4 cells of gonococci with specific isotopes for studies of metabolic and biochemical changes.